Monetary Union Viability: A Criterion Proposal. (11th July 2014) - Alonso, Alberto; Guzmán, Vanesa
Abstract We propose a model that represents the dynamic behaviour of a monetary union comprising two countries whose natural interest rates are initially unequal. This initial disparity and the subsequent application of a common monetary policy generate different national inflation rates and lead to losses of competitiveness, foreign deficits, and the indebtedness of one country with respect to the other. We propose as a viability criterion for the modelled monetary union a combination of non‐explosive foreign debt and the ability of the central bank to neutralize the contracting effects of taking on additional debt to avoid falling into a liquidity trap.